Características físico-químicas de cultivares de feijão (Phaseolus vulgaris L.), e efeitos biológicos da fração fibra solúvel - Prolla, Ivo Roberto Dorneles (2006)
Raw seeds of sixteen common bean (Phaseolus vulgaris L.) cultivars were evaluated along two consecutive harvests (2001/2002 and 2002/2003) concerning their physicochemical characteristics, as well as the effect of cooking and storage conditions on starch and dietary fiber contents. Serum lipids and blood glucose levels were also evaluated in normolipidemic-normoglycemic rats witch were fed diets containing bean cultivars with different soluble fiber/total fiber ratios (SF/TF): Pérola diet (0.11), Diamante Negro diet (0.19) and Iraí diet (0.26); control group was fed a standard diet (with insoluble fiber). Except for dry matter, moisture, and total dietary fiber, cultivars kept their chemical characteristics between harvests. Regarding similarity among macronutrient levels (crude protein-CP, total dietary fiber, insoluble dietary fiber, soluble dietary fiber-SF, digestible starch-DS, and resistant starch-RS) seeds from harvests 2001/2002 and 2002/2003 were categorized into four different groups; the same was done for micronutrients (Fe, Zn, Mn, Cu, Ca, Mg, and P), and four groups were also identified. Guateian 6662 and Rio Tibagi were considered the cultivars with the best nutritional profile (highest levels of CP, SF, DS, Fe, and Zn). Storage under refrigerated or freezing conditions did not change fiber content of cooked beans, but decreased their DS content and increased RS content, mainly in seeds with low RS levels before cooking. Concerning biological response, rats fed bean diets experienced lower values for serum cholesterol (P<0.05) and lower glycemic indexes (P<0.05). It was also observed a similar weight gain among groups, however animals fed bean based diets showed lower fat retention (P<0.05). The effects of bean diets on experimental groups were more remarkable in animals fed Iraí diet (SF/TF: 0.26).